Perencanaan dan Pengendalian Jadwal dengan Menggunakan Program Microsoft Project Profesional 2013 (Studi Kasus: Struktur Gedung Pelayanan Terpadu Universitas Tribhuwana Tunggadewi Malang) - Nahak , Antonius ; Rasidi , Nawir; Wijaya , Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
A project can be said to be successful if the implementation process can be completed on time as planned. Inappropriate planning and control in a project can result in waste of resources and will also lead to failure in achieving the objectives of the project. Therefore, in planning a project schedule using the 2013 Microsoft Project Professional Program, the first thing to do is to enter the activity data that will be carried out such as the project start date, type of activity, duration of time, resources, and so forth. In the planning and controlling stages of the project schedule using the 2013 Professional Project, one method that can be done is to add overtime to an activity if there is a delay. From the planning and control of the schedule carried out on the Integrated Service Building Structure building project at the University of Tribhuwana Tunggadewi Malang using the 2013 Microsoft Project Program for 68 days, and in the control phase there are several work items that experience a Critical trajectory. extra overtime hours. So that work items that experience a critical trajectory can be overcome.